Réfugiés et migrants dans les églises protestantes évangéliques libanaises : Recompositions identitaires et enjeux sociaux - Fatiha Kaoues (L’Année du Maghreb, 2014)
In recent years, Lebanon has experienced an unprecedented evangelical Protestant activity. This country enjoys freedom of religious expression higher than that of its neighbours. What’s more, hundreds of thousands of refugees and foreign migrants from around the world reside in Lebanon. Therefore, these foreigners are ideal targets for evangelical missionaries who wish to convert them. Thus, refugees and migrant domestic workers, who are welcomed in these churches develop new forms of sociability. This article analyses the integration of foreign workers and refugees into evangelical structures, which offer new social horizons and possibilities.